(untitled) (Palíndromo, 2022)
The following artistic proposition addresses the work "Disarming Guatemala’s Coat of Arms", a theoretical and practical re-reading of Guatemala’s independence. This patriotic symbol "reinforces" a national identity with which the population does not identify and now demands another symbology, artistically disarming the elements present in the current coat of arms. Removing symbols of violence, death, and conquest, I seek to open space for elements of revolution, freedom, and strength from the collective struggles of the popular indigenous movements, which have arduously gone through all kinds of military and social oppression, but always remain firm and strong in their purposes. In this work I develop a new coat of arms, made up of elements of revolutionary purpose.